Kidney Calculi in Iranian Children: A Multicentric Report: Kidney Calculi in Iranian Children - Akhavan Sepahi, Mohsen; Sharif, Amin Sadat; Hooman, Nakysa; Azarfar, Anoush; Mohammadjafari, Hamid; Ghasemi, Khadijeh; Esteghamati, Maryam; Pournasiri, Zahra; Dalirani, Reza; Esfandiar, Nasrin; et al. (Journal of Pediatric Nephrology, 2023)
Background and Aim: Studies on the prevalence of kidney stones in Iranian children are limited. Children with nephrolithiasis have a high risk of recurrent stones; therefore, a thorough evaluation is warranted. Due to the paucity of data on Iranian children, this study aims to investigate the prevalence of kidney stones in this population. Methods: This cross-sectional study examined the prevalence of kidney stones among outpatients and inpatients at various university centers in Iran from March to December 2019. Twenty-six pediatric nephrologists from 13 centers participated and completed a questionnaire on the total number of inpatients and outpatients and the number of patients with kidney stones. The diagnosis was based on radiological results. Results: A total of 97 912 patients were included, with 20327 hospitalized and 77585 outpatients. Of all patients, 2.86% had kidney stones, the prevalence of which was 1.5% in inpatients and 3.2% in outpatients. This figure is about 1% more than Iran’s past reports. Inpatient stones in Kerman City, Iran (3.65%) and outpatients in Zahedan City, Iran (16.4%) were the most common. The study lacked data on age and gender. The main results are the total and setting-specific prevalences, and regional variations suggesting environmental and genetic factors. Conclusion: This large study examined kidney stone prevalence in Iranian children, the total prevalence of which is 2.86%. Given the limited data and rising trend, more extensive studies with the collaboration of additional centers are recommended. Demographic characteristics, such as age, sex, stone composition, family history, and diet should be examined.